Fluid Mixing Process Based on Programmable Logic Controller as Training Kit for Electrical Engineering Education Students - Rusimamto, Puput Wanarti; Munoto, Muchlas Samani; Buditjahjanto, I G.P. Asto; Ekohariadi; Luthfiyah, Nurlaela; Mohammad Nuh, Endryansyah (International Journal of Integrated Engineering, 2021)
The Department of Electrical Engineering, State University of Surabaya (Unesa) is developing a laboratory, including a control system laboratory. The team of teaching regulatory techniques prepares themselves by making a PLC practicum module accompanied by a PLC training kit. With the aim that students know and understand the application of regulatory systems in industry. This can foster student learning motivation in attending lectures and greatly support student competence before entering the world of work. The type of research used is development research by producing a product prototype in the form of a fluid mixing process training kit. The steps taken are designing, making tools, integrating software to hardware and validating the tools. The result of the research is that the fluid mixing process training kit has worked according to the instructions given and is suitable for use as a learning medium.